Interactive Effects of Temperature and UV Radiation on Photosynthesis of Chlorella Strains from Polar, Temperate and Tropical Environments: Differential Impacts on Damage and Repair - Wong, Chiew Yen; Teoh, Ming Li; Phang, Siew Moi; Lim, Phaik Eem; Beardall, John (Public Library of Science, 2015)
Global warming and ozone depletion, and the resulting increase of ultraviolet radiation (UVR), have far-reaching impacts on biota, especially affecting the algae that form the basis of the food webs in aquatic ecosystems. The aim of the present study was to investigate the interactive effects of temperature and UVR by comparing the photosynthetic responses of similar taxa of Chlorella from Antarctic (Chlorella UMACC 237), temperate (Chlorella vulgaris UMACC 248) and tropical (Chlorella vulgaris UMACC 001) environments. The cultures were exposed to three different treatments: photosynthetically active radiation (PAR; 400-700 nm), PAR plus ultraviolet-A (320-400 nm) radiation (PAR + UV-A) and PAR plus UV-A and ultraviolet-B (280-320 nm) radiation (PAR + UV-A + UV-B) for one hour in incubators set at different temperatures. The Antarctic Chlorella was exposed to 4, 14 and 20C. The temperate Chlorella was exposed to 11, 18 and 25C while the tropical Chlorella was exposed to 24, 28 and 30C. A pulse-Amplitude modulated (PAM) fluorometer was used to assess the photosynthetic response of microalgae. Parameters such as the photoadaptive index (Ek) and light harvesting efficiency () were determined from rapid light curves. The damage (k) and repair (r) rates were calculated from the decrease in PSIIeff over time during exposure response curves where cells were exposed to the various combinations of PAR and UVR, and fitting the data to the Kok model. The results showed that UV-A caused much lower inhibition than UV-B in photosynthesis in all Chlorella isolates. The three isolates of Chlorella from different regions showed different trends in their photosynthesis responses under the combined effects of UVR (PAR + UV-A + UV-B) and temperature. In accordance with the noted strain-specific characteristics, we can conclude that the repair (r) mechanisms at higher temperatures were not sufficient to overcome damage caused by UVR in the Antarctic Chlorella strain, suggesting negative effects of global climate change on microalgae inhabiting (circum-) polar regions. For temperate and tropical strains of Chlorella, damage from UVR was independent of temperature but the repair constant increased with increasing temperature, implying an improved ability of these strains to recover from UVR stress under global warming.